PELITA INTERACTIVE MEDIA FOR BEGINNING READING IN ELEMENTARY SCHOOL - Endah Saadah; Lutfi Nur; Dian Indihadi (Jurnal Cakrawala Pendas, 2025)
This study investigates the necessity for developing “PELITA” (Early Literacy Adventure), a contextual and engaging digital media aimed at enhancing early reading instruction in primary schools. Early literacy, particularly beginning reading, forms a fundamental pillar of academic success. However, Indonesia’s low literacy performance highlights the urgent need for innovative learning tools that can boost student motivation and participation. Adopting the Systematic Literature Review (SLR) method based on PRISMA 2020 guidelines, this study synthesizes relevant research to identify key characteristics of effective media. The findings reveal that successful digital tools incorporate narrative elements, appealing visuals, and gamified components that enhance phonological awareness, comprehension, and learner engagement. Despite their potential, culturally grounded literacy tools remain scarce. This review offers a scientific contribution by proposing a conceptual foundation for developing localized and child-friendly literacy media. The development of PELITA is thus positioned as a promising response to these gaps, emphasizing the importance of fun, adaptive, and developmentally appropriate media design. The results provide valuable insights for educators, media developers, and policy makers committed to fostering an inclusive and sustainable literacy ecosystem.